Development of Feed and Organic Fertilizer Bioindustry Based on Cocoa-Goat Integration - Gunawan .; Chalid Talib (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
The cacao farmers generally experienced problems on low cacao productivity and hence farmer’s income. The aim of this paper is to describe concept on the development of feed and organic fertilizer bioindustry based on cacao-goat integration to enhance productivity and farmer’s income. The potential cacao-goat integration covers 1.4 million hectares of cacao plantation and 7.8 million head of goats in nine provinces. Implementation of cacao-goat integration allows to use cacao biomass as feed for goats, and goat’s manure can be applied as fertilizer for cacao plantation. Bioindustry of feed is developed from 3.3 million tons biomass of cacao that consisted of 1.9 million tons of cacao pods and 1.4 million tons of cacao leaves. Bioindustry productions of solid and liquid organic fertilizer are 0.6 million tons and 344 million liters, respectively. The development of feed and organic fertilizer bioindustry is appropriate to improve cacao and goat productivities lead to increase farmer’s income.